Systems librarianship a practical guide for librarians - Gonzales, Brighid M. (Practical guides for librarians ;, 2020)
"Geared toward interested LIS students, new graduates, and new Systems Librarians, this book lays out basic foundational knowledge, as well as practical information on common projects like migrating a system and technology planning, that will guide new Systems Librarians as they begin their careers in library technology"--